Natural dialogue and natural polemic: points of tension and understanding between liberals and communitarians - Hinostroza Rivera, Dino Arturo (2022)
The scoope of this writing is to clarify certain similarities and differences between the two main political ideologies of the West, namely, liberalism and communitarianism, and to extend a natural dialogue bridge between the centrist positions of this axis and a natural controversy between the positions most radical of such systems of ideas. For this, we will trace a historical line of thought of both systems of ideas and we will identify a demarcation line between the moderate and radical positions of both systems of ideas. It should be noted that this historical outline does not intend to be univocal, nor will it try to define the system of ideas of each of the cited authors, but rather to define some similarities and differences between the nuances of each system of ideas that make possible or impossible the dialogue as the political means par excellence. Finally, we emphasize that this writing may be insufficient, in practical terms, to explain the political reality, since we do not contemplate the empirical variables, or interests.